Toward industrial production of isoprenoids in Escherichia coli: Lessons learned from CRISPR‐Cas9 based optimization of a chromosomally integrated mevalonate pathway. Issue 4 (7th February 2018) - Alonso‐Gutierrez, Jorge; Koma, Daisuke; Hu, Qijun; Yang, Yuchen; Chan, Leanne J. G.; Petzold, Christopher J.; Adams, Paul D.; Vickers, Claudia E.; Nielsen, Lars K.; Keasling, Jay D.; Lee, Taek S.
Abstract: Escherichia coli has been the organism of choice for the production of different chemicals by engineering native and heterologous pathways. In the present study, we simultaneously address some of the main issues associated with E. coli as an industrial platform for isoprenoids, including an inability to grow on sucrose, a lack of endogenous control over toxic mevalonate (MVA) pathway intermediates, and the limited pathway engineering into the chromosome. As a proof of concept, we generated an E. coli DH1 strain able to produce the isoprenoid bisabolene from sucrose by integrating the cscAKB operon into the chromosome and by expressing a heterologous MVA pathway under stress‐responsive control. Production levels dropped dramatically relative to plasmid‐mediated expression when the entire pathway was integrated into the chromosome. In order to optimize the chromosomally integrated MVA pathway, we established a CRISPR‐Cas9 system to rapidly and systematically replace promoter sequences. This strategy led to higher pathway expression and a fivefold improvement in bisabolene production. More interestingly, we analyzed proteomics data sets to understand and address some of the challenges associated with metabolic engineering of the chromosomally integrated pathway. This report shows that integrating plasmid‐optimized operons into the genome and making them work optimally is not a straightforward task and any poor engineering choices on the chromosome may lead to cell death rather than just resulting in low titers. Based on these results, we also propose directions for chromosomal metabolic engineering. Abstract : Some of the main issues associated with E. coli as an industrial platform for isoprenoids were addressed, including an inability to grow on sucrose, a lack of endogenous control over toxic mevalonate pathway intermediates, and the limited pathway engineering into the chromosome. A new methodology for metabolic engineering of chromosomally integrated pathways is proposed using CRISPR‐Cas9 to switch biological parts of the integrated pathway and lessons were presented in optimizing heterologous pathways in the chromosome.